STRATEGI PEMBELAJARAN BERBASIS PJBL, BERBASIS(PBL), PEMBELAJARAN KOLABORATIF, BELAJAR SAMBIL BERMAIN (PBL) - Sriliza Sriliza; Rahmadifa Rahmadifa; Ulan Dari (JIP: Jurnal Ilmu Pendidikan, 2025)
This research aims to analyze the implementation and effectiveness of four 21st-century learning strategies, namely Project-Based Learning (PjBL), Problem-Based Learning (PBL), Collaborative Learning, and Play-Based Learning (PbL) in the context of elementary school education. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that all four strategies have their own strengths: PjBL encourages creativity and critical thinking skills through real projects; PBL develops analysis and data-based problem-solving skills; Collaborative Learning fosters cooperation, communication, and empathy; while PbL creates enjoyable learning that is appropriate for children's development. The integration of these four strategies produces meaningful, holistic, and contextual learning, in line with the principles of the Independent Curriculum. Teachers play an important role as facilitators who must be able to design active and reflective learning. The results of this study recommend the application of an integrated approach in thematic learning as an effort to create intelligent, adaptive students who are ready to face global challenges.